2011
DOI: 10.1586/erd.10.75
|View full text |Cite
|
Sign up to set email alerts
|

State of the art in hard-on-hard bearings: how did we get here and what have we achieved?

Abstract: Total hip arthroplasty has shown excellent results in decreasing pain and improving function in patients with degenerative disease of the hip. Improvements in prosthetic materials, designs and implant fixation have now resulted in wear of the bearing surface being the limitation of this technology, and a number of hard-on-hard couples have been introduced to address this concern. The purpose of this article is to review the origins, development, survival rates and potential advantages and disadvantages of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 269 publications
0
20
0
Order By: Relevance
“…In addition, the THA patient population is becoming younger, more active, and more obese, and subsequently placing higher demands on the prosthesis and specifically the bearing surface [3]. Alternative bearings in THA have been developed in an attempt to reduce wear-related issues and improve implant longevity [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the THA patient population is becoming younger, more active, and more obese, and subsequently placing higher demands on the prosthesis and specifically the bearing surface [3]. Alternative bearings in THA have been developed in an attempt to reduce wear-related issues and improve implant longevity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent bearing surface combinations include metal-on-polyethylene (MOP) and ceramic-on-polyethylene (COP) with cross-linked polyethylene [5], ceramic-on-ceramic (COC) [6,7], ceramic-on-metal (COM) [4] and metal-on-metal (MOM). Legitimate concerns with MOM bearing couples including ion production and adverse local tissue reactions have led to a drastic reduction in the usage of metal liners [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A previous comparison of four bearings revealed that ceramic-on-polyethylene bearing couple achieved the best results for revision for any reason (98.1%). 9 Similar to a previous description, the survival of the ceramic-on-polyethylene bearings in the Zweymüller-Plus system was relatively high in our study (99.0%).…”
Section: Discussionmentioning
confidence: 93%
“…These articulations have been in use in orthopedics for over 50 years [1]. They enjoyed a resurgence over the past decade, promising greater longevity and higher activity levels.…”
mentioning
confidence: 99%